Sentiment Analysis on Beauty Product Review Using Modified Balanced Random Forest Method and Chi-Square - Antika Putri Permata Wardani; Adiwijaya Adiwijaya; Mahendra Dwifebri Purbolaksono (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Internet users in Indonesia have used e-commerce services to buy various products. For example, one website that provides information services about women's beauty products is Female Daily. On the website, there are reviews of beauty products. The review feature is one feature that helps users in determining which beauty products to buy. Unfortunately, many reviews will take a long time to read, and it is almost impossible for users to read all the information. Therefore, research is needed to make it easier for users to consider products such as sentiment analysis. Sentiment analysis aims to classify opinions, namely, user reviews, into positive, neutral, and negative opinions. In this study, sentiment analysis uses the Modified Balanced Random Forest(MBRF) and Chi-square method as feature selection. The best model from this study produces an average accuracy and an average f1-score of 81.75% and 71.90%, respectively.